Chinese standard requirements on indoor environmental quality for assessment of energy-efficient buildings. Issue 2 (April 2014) - Li, Guo-Zhu; Wang, Qing-Qin; Wang, Jun-Liang
Indoor environmental quality (IEQ) is crucial to the occupants' comfort and health. However, the energy consumption of indoor environment must not be compromised whilst achieving a comfortable indoor environment. In the Chinese Standard for Energy Efficient Building Assessment ( GB/T 50668-2011 ) (SEEBA), the energy-efficient performance of indoor environment is predicated on the requirement of achieving a comfortable and healthy environment for occupants in buildings. This standard is formulated with a view to assess the energy efficiency grade of residential buildings and public buildings. In this paper, the evaluation index system and assessment method of SEEBA are introduced, and the provisions in relation to indoor environment in SEEBA are discussed in detail, including the prerequisite items (temperature, humidity, lighting, ventilation and pollutant concentration), standard items (mould growth, temperature, natural lighting and natural ventilation) and outstanding items (automatic ventilation control system for underground garages, use phase change materials to store heat and other functional materials for moderating indoor humidity for residential buildings and automatic building management system to regulate air changes in public buildings). SEEBA has an essential role to provide bench mark standard for evaluation of energy-efficient buildings, providing guidance and promoting the development of healthy energy-efficient buildings in China. SEEBA can be used as a reference standard for energy efficiency assessment of buildings also suitable in many parts of the world.